Merajut Jati Diri Profetis Guru Agama Katolik Dalam Era Milenial - Keristian Dahurandi (STIPAS St. Sirilus Ruteng, 2019)
There are two dangers of millennial era: economism and simulacra. Economism can change paradigm of thinking: from “unconditional love” to profit-capitalist calculations. A created simulacra is capable of reconstructing society to be a hyperreality world, that is, a society which does not understand reality as such but what the realtity is referred to or designed for economic interests (consumptive society). This danger becomes a serious pastoral challenge toprophetic role of Catholic Religion Teacher. One of possible solutions is to strengthen teacher ’sidentity through some modes: first, to live out the task as a vocation; second, living acovenant spirituality; third, being an agent of God’s image/likeness; fourth, to bear witness as disciples of Christ. These four modes, undoubtedly, will help Catholic teachers to play a professional and prophetic role.